Article 310 Law Number 22 Of 2009: Legal Responsibility Of Parents Of Children In Traffic Accidents In Indonesia - Danny PD, Shidiq Ardhiansyah; Kurniawan, Itok Dwi (Faculty of Law, Universitas Muhammadiyah Pontianak, 2023)
Children are the best hope for the future of any country, community group or family; they are a gift from God to those blessed by their presence. The emotional, mental, and social well-being of their children primarily falls within the purview of the child's parents. Children's journey towards adulthood and the development of their capacity to live independently is the responsibility of parents. This article was created with the aim of enlightening readers regarding the responsibilities of parents for petty theft committed by their children while they are under their supervision and while the children are in their care. Researchers will use normative legal research techniques to ensure that they have a comprehensive understanding of the criteria they will use to analyze results and find solutions to the problems they pose in their research. Legal case analysis, legal literature analysis, and regulatory analysis are some of the methodologies used. The authors of this study draw several conclusions regarding children's responsibility for their financial well-being as perpetrators of criminal acts. The author then outlines the need to dispel doubts regarding responsibility towards minors, while emphasizing the need to monitor children's psychological development. The uniformity of children's responsibilities in long-form fairy tales is a stumbling block for writers.